Apolipoprotein E promotes subretinal mononuclear phagocyte survival and chronic inflammation in age‐related macular degeneration - Olivier Levy; Bertrand Calippe; Sophie Lavalette; Shulong J Hu; William Raoul; Elisa Dominguez; Michael Housset; Michel Paques; José‐Alain Sahel; Alexis‐Pierre Bemelmans; Christophe Combadiere; Xavier Guillonneau; et al. (EMBO Molecular Medicine)
Abstract Physiologically, the retinal pigment epithelium (RPE) expresses immunosuppressive signals such as FAS ligand (FASL), which prevents the accumulation of leukocytes in the subretinal space. Age‐related macular degeneration (AMD) is associated with a breakdown of the subretinal immunosuppressive environment and chronic accumulation of mononuclear phagocytes (MPs). We show that subretinal MPs in AMD patients accumulate on the RPE and express high levels of APOE. MPs of Cx3cr1−/− mice that develop MP accumulation on the RPE, photoreceptor degeneration, and increased choroidal neovascularization similarly express high levels of APOE. ApoE deletion in Cx3cr1−/− mice prevents pathogenic age‐ and stress‐induced subretinal MP accumulation. We demonstrate that increased APOE levels induce IL‐6 in MPs via the activation of the TLR2‐CD14‐dependent innate immunity receptor cluster. IL‐6 in turn represses RPE FasL expression and prolongs subretinal MP survival. This mechanism may account, in part, for the MP accumulation observed in Cx3cr1−/− mice. Our results underline the inflammatory role of APOE in sterile inflammation in the immunosuppressive subretinal space. They provide rationale for the implication of IL‐6 in AMD and open avenues toward therapies inhibiting pathogenic chronic inflammation in late AMD.